Quantifying the Value of RFID and the EPCglobal Architecture Framework in Logistics - Uckelmann, Dieter; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
The “EPCglobal Architecture Framework” is currently the most accepted technical approach to the Internet of Things and provides a solid foundation for building Business-to-Business information networks based on unique identifications of ‘things’. Lately, the vision of the Internet of Things has been extended to a more holistic approach that integrates sensors as well as actuators and includes non-business stakeholders. A detailed look at the current state of the art in research concerning cost and benefit estimations is provided and the limits of Cost Benefit Sharing for RFID-based IT-infrastructures are explained. In this work a market driven evaluation based on sales potential of information is developed. Simple technical means for aggregation of micro values to a billable amount are discussed. The requirements for electronic billing infrastructure are defined and a matching e-billing solutions for an evaluation scenario is presented, providing a technical infrastructure to evaluate and bill product-related information in a future Internet of Things, based on an extended EPCglobal Architecture. Further opportunities and threats are discussed to provide an overview of its future potential. As a result it will contribute to the sustainable success of the Internet of Things itself.
Limiting obstacles to success of RFID and the EPCglobal Network in  logistics -- Electronic information sharing in supply networks -- Performance measurement and cost benefit analysis for RFID and Internet of Things implementations in logistics -- Preconditions for creating economic value through market-driven information pricing and billing in B2B scenarios -- Modelling and prototyping an integration of billing mechanisms into the EPCglobal Network Architecture -- Evaluation of the technical billing-enabled Internet of Things framework.
Keywords: Engineering economics; Engineering economy; Production management; E-commerce.; Microwaves; Optical engineering; Engineering Economics, Organization, Logistics, Marketing; Operations Management; e-Commerce/e-business.; Microwaves, RF and Optical Engineering